1994
DOI: 10.1111/j.1365-2958.1994.tb00469.x
|View full text |Cite
|
Sign up to set email alerts
|

Signal peptides: exquisitely designed transport promoters

Abstract: Prokaryotic proteins destined for transport out of the cytoplasm typically contain an N-terminal extension sequence, called the signal peptide, which is required for export. It is evident that many secretory proteins utilize a common export system, yet the signal sequences themselves display very little primary sequence homology. In attempting to understand how different signal peptides are able to promote protein secretion through the same pathway, the physical features of natural signal sequences have been e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
175
0
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(179 citation statements)
references
References 110 publications
3
175
0
1
Order By: Relevance
“…A ''tighter'' helical conformation induced by bulky, hydrophobic residues such as Ile may have buried the cleavage site within the lipid matrix thus restraining it from gaining access to the exocytoplasmic active site of SPase. These findings are in agreement with previous reports [42][43][44] that overall length of the central core and sequence hydrophobicity determine the in vivo translocation efficiency of export rates. These observations provide the basis for the poorer export rates of the bulky X þ1 and for the peculiar behavior of other less bulky but hydrophilic residues such as Gly.…”
Section: Export Features Of Ss-x 11 -Cytochrome B 5 Isoformssupporting
confidence: 94%
“…A ''tighter'' helical conformation induced by bulky, hydrophobic residues such as Ile may have buried the cleavage site within the lipid matrix thus restraining it from gaining access to the exocytoplasmic active site of SPase. These findings are in agreement with previous reports [42][43][44] that overall length of the central core and sequence hydrophobicity determine the in vivo translocation efficiency of export rates. These observations provide the basis for the poorer export rates of the bulky X þ1 and for the peculiar behavior of other less bulky but hydrophilic residues such as Gly.…”
Section: Export Features Of Ss-x 11 -Cytochrome B 5 Isoformssupporting
confidence: 94%
“…Numerous theoretical and experimental studies have established the key tenets of bacterial signal peptides (reviewed in Izard and Kendall, 1994), but thylakoidal signal peptides have not been analysed in detail and no mutagenesis studies have been reported. Although only three proteins are known to be transported by the Sec pathway in chloroplasts (PC, 33-kDa PSII protein, and PSI-F), a number of lumenal proteins have been cloned in cyanobacteria, and the sequencing of three algal chloroplast genomes has shown that several lumenal proteins are encoded with signal peptides.…”
Section: Resultsmentioning
confidence: 99%
“…A large number of studies on prokaryotic Sec signals (reviewed by Izard and Kendall, 1994) have shown quite clearly that the distribution of basic residues is central to the efficiency with which the signal peptide functions. A net positive charge in the N-terminus is important for efficient targeting, with greater charges resulting in more efficient targeting.…”
Section: Discussionmentioning
confidence: 99%
“…This ORF ends with a TAA stop codon in position 1270 and potentially encodes a 284 amino acid polypeptide precursor with a calculated molecular mass of 27.6 kDa. The first 22 N-terminal amino acids exhibit structural similarities with signal sequences of exported proteins (Izard & Kendall, 1994;Pugsley, 1993). The putative site of cleavage by signal peptidase is indicated with an arrow in Fig.…”
Section: Cloning and Genomic Mapping Of Erpmentioning
confidence: 99%